English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-24 15:47:13 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

Let's see:

e^f(x) f'(x) -- does this remind you of the chain rule much? The antiderivative is simply e^f(x) + C in these cases -- in particular, ∫e^(sin x) cos x dx = e^(sin x) + C

2007-01-24 15:53:16 · answer #1 · answered by Pascal 7 · 1 0

use u-substitution:
u = sin(x), then du = cos(x)dx
so integrate du e^u
= e^u + C
resub in u
= e^sin(x) + C

2007-01-24 23:57:30 · answer #2 · answered by Anonymous · 0 0

integral of u.v = u (int v dx) - int [int v dx (du/dx)]
u = cosx
v = e^sinx
now solve the problem with this formula

2007-01-25 00:46:57 · answer #3 · answered by Anjali 2 · 0 0

fedest.com, questions and answers